2016
DOI: 10.1002/hipo.22614
|View full text |Cite
|
Sign up to set email alerts
|

Functional cross‐hemispheric shift between object‐place paired associate memory and spatial memory in the human hippocampus

Abstract: VR environment and task‐dependent cross‐hemispheric functional shift in the hippocampus. Top: Side view of the east building and examples of objects used the current study. Middle: Sagittal (right) and coronal (left) section showing the peak activity in the left hippocampus during the object‐cueing period. Bottom: Sagittal (right) and coronal (left) section showing the peak activity in the right hippocampus during the spatial memory period. L and R on the left upper corners respectively denote left and right h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We then grand‐averaged the P1w peak amplitude for EC and FG stimulation separately in each individual patient, when the stimulation is delivered to more than one electrode pair in each region. Recently, Lee, Ryu, Lee, Kim, and Lee () showed in human fMRI study that the efficient retrieval of object–place paired associate memory was correlated with the BOLD response of the left hippocampus, whereas the efficient retrieval of relatively pure spatial memory was correlated with the right hippocampal BOLD response, suggesting that the left and right hippocampus process qualitatively different information for remembering episodic events in space. Thus, we expect that both the left and right hippocampus may have an important role in episodic memory function.…”
Section: Methodsmentioning
confidence: 99%
“…We then grand‐averaged the P1w peak amplitude for EC and FG stimulation separately in each individual patient, when the stimulation is delivered to more than one electrode pair in each region. Recently, Lee, Ryu, Lee, Kim, and Lee () showed in human fMRI study that the efficient retrieval of object–place paired associate memory was correlated with the BOLD response of the left hippocampus, whereas the efficient retrieval of relatively pure spatial memory was correlated with the right hippocampal BOLD response, suggesting that the left and right hippocampus process qualitatively different information for remembering episodic events in space. Thus, we expect that both the left and right hippocampus may have an important role in episodic memory function.…”
Section: Methodsmentioning
confidence: 99%
“…Prior volumetric and functional neuroimaging studies revealed that the hippocampus was structurally and functionally asymmetric, suggesting that the left and right hippocampi are involved in qualitatively different aspects of memory formation. The right hippocampus is thought to be involved in processing of spatial memory, and the left hippocampus in the processing of verbal memory . Our current study supports the idea that the right hippocampus is involved in visuospatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…There may be differences in hemispheric specialization in the primate hippocampus. Human studies indicate that exploration and recognition show laterality, with the right hippocampus preferentially activating during exploration of new scenes and the left hippocampus preferentially activating during repeated scenes (Lee et al, 2016). The right hippocampus also seems to be preferentially recruited for large-scale, allocentric navigation whereas the left hippocampus is recruited for temporal sequence memory, egocentric navigation, autobiographical experience memory and match-mismatch associative memory (Iglói et al, 2010;Kumaran & Maguire, 2007;Lehn et al, 2009;Maguire & Frith, 2003).…”
Section: Limitationsmentioning
confidence: 99%